BOLOGNA PROCESS: PRESENT STAGE - Valentin I. Baydenko (Высшее образование в России, 2016)
The main goal of the article is to highlight the key trends in implementing European%wide reforms of higher education within the Bologna Process, since 2015 - now with Belarus as a member state. The present stage of the Bologna transformations (2015- 2020) is based on a new vision of the European Higher Education Area. Significantly, it features a growing relevance of learning and teaching in the conceptual vein of a new higher education focus on learning outcomes, competence%based and student%centered education process. The added emphasis should be on academic staff development and support to encourage them to achieve excellence in teaching and improve didactic competences. The proposed publication somewhat expands the Bologna process context to the scope of the current “academic revolution” (F. Altbach) caused by the growing role of globalization in modern higher education (D. Neubauer).